Lipase production from Aniba canelilla endophytic fungi, characterization and application of the enzymatic extract (Research, Society and Development, 2022)
Endophytic fungi (EF) have a notable capacity to produce active molecules of industrial importance, such as hydrolytic enzymes. In this study we investigated the production of lipase by EFs isolated from the Amazonian species Aniba canelilla (Lauraceae), characterized the enzymatic extract obtained from the most promising fungus, and applied the lipolytic extract as a biocatalyst in the transesterification reaction for biodiesel production. The fungi were submitted to enzymatic screening in solid medium and in submerged fermentation to assess their lipase production. A total of 292 fungi were tested in solid media. Lipolytic activity was detected in 74% of the fungi cultivated in liquid media, 18 of which showing promising enzymatic production. The best lipase producer, Endomelanconiopsis endophytica QAT_7AC, was identified by sequencing of the ITS region. After adjusting the bioprocess conditions, E. endophytica QAT_7AC produced 2,415.5 U/mL of lipase after 72 h. The enzymatic extract showed higher lipolytic activity under pH 8.0 and 40 oC. The extract was applied as a biocatalyst in a transesterification reaction performed at 40 oC, with ethanol and waste cooking oil (3:1). The biodiesel yield was found to be 87% after 2 h rection when the fungal enzyme was used and 89% with the commercial biocatalyst. The endophytic fungi isolated from A. canelilla proved themselves to be biotechnologically relevant, as they can be explored as potential producers of lipases. The lipolytic extract can be applied in the synthesis of biodiesel using waste cooking oil.